Susceptibility of Malassezia pachydermatis Clinical Isolates to Allopathic Antifungals and Brazilian Red, Green, and Brown Propolis Extracts - Deegan, Kathleen Ramos; Fonseca, Maisa Santos; Oliveira, Diogo Coelho Pádua; Santos, Laerte Marlon; Fernandez, Clara Couto; Hanna, Samira Abdallah; Machado, Bruna Aparecida Souza; Umsza-Guez, Marcelo Andrés; Meyer, Roberto; Portela, Ricardo Wagner (Frontiers in Veterinary Science, 2019)
Clinical mycoses treatment is associated with issues such as negative side effects, high cost, prolonged treatment, and resistant strain selection. Malassezia pachydermatis is the most frequently isolated yeast in cases of canine otitis and dermatitis. The number of fungal strains exhibiting primary resistance to several drugs in vitro is increasing. Propolis has a diverse chemical composition and well-known therapeutic properties against mycoses. An alternative method for producing propolis extracts using supercritical fluid has higher selectivity, yielding extracts with fewer pollutant residues. This study therefore aimed to evaluate the in vitro susceptibility profile of M. pachydermatis clinical isolates to precharacterized supercritical and ethanolic extracts. Three types of Brazilian propolis extracts (green, red, and brown) and commercial allopathic antifungals were used in this investigation. We used the microdilution broth technique to evaluate the susceptibility profile of the yeasts. The minimum inhibitory concentration (MIC) of the brown propolis ethanolic extract was ≥16 μg/mL for all isolates. The MICs of fluconazole, ketoconazole, itraconazole, and amphotericin B ranged from 8 to >64 μg/mL, 0.032–4 μg/mL, 0.0313–16 μg/mL, and 1–2 μg/mL, respectively. The MICs of ethanolic red propolis extracts were lower than those of supercritical red propolis extracts. However, the green propolis ethanolic extract had more pronounced fungicidal activity. Isolates with lower susceptibility to commercial fungicides were inhibited by red and green propolis extracts. These results indicate that propolis can potentially be used in in vivo experiments as a promising therapeutic agent against M. pachydermatis infections.